The Effect of Promotion, Price and Product Quality on Wardah Skincare Purchasing Decisions - Arum, Jovita Sekar; Achmad, Nur (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The Indonesian beauty industry has experienced very rapid development in recent years. This can be seen from the increasing number of local and international beauty brands offering various facial skin care products and services. The aim of this research is to find out whether there is an influence of promotion, price and purchasing decisions on facial skin care products which is moderated by brand image. This research method uses a quantitative type of research with the aim of collecting and analyzing numerical data to answer questions. Primary data was collected through distributing questionnaires online. The population used in this research were FEB UMS students. The sample in this study were Feb UMS students who had used Wardah brand skincare products 1-2 times or >2 times. To determine the research sample size, the researcher measured the size of the sample that would be researched. Referring to Hair's opinion, namely, the number of indicators x 5. In this study the number of indicator questions was 21 items, so 21 indicators x 5, namely 105 respondents. This research uses Structural Equation Model (SEM) analysis techniques with Partial Least Square (PLS), a smart PLS software tool to analyze and process data. From the research results, it was found that promotions and prices do not have a significant influence on purchasing decisions. Product quality has an influence on purchasing decisions. Brand image has a positive and significant influence on purchasing decisions. And brand image is able to mediate the variables of promotion, price and product quality on Wardah skincare purchasing decisions.